Perancangan Pembangkit Listrik Tenaga Surya (PLTS) untuk Suplai Daya Sistem Pemberian Pakan Ikan Otomatis - Galuh Prawestri Citra Handani; Binar Surya Gumilang; Afidah Zuroida (Politeknik Negeri Malang, 2022)
In aquaculture production, the number of fish cultivated in freshwater ponds contributes up to 1.1 million tonnes. Catfish(Clarias sp.) is a type of freshwater fish that is quite popular in the cultivation process. The feeding system still has many shortcomings, suchas the amount of feed that is not regular and the timing of feeding which is prone to being irregular. The automatic feeding system requiresa continuous power supply without being interrupted by blackouts from the PLN electricity network. One of the power supply alternatives isto create a power generation system (PLTS). Based on the research results, the solar module capacity is 500 Wp for 1 polycrystalline typemodule, the solar charge controller rating is 20 A, the VRLA battery capacity is 200Ah 12 V KIJO, and the inverter capacity is 850 VA. Theresults of calculations and planning of PLTS can supply electricity with a load power of 1867 watts/hour.